Synchronous Presentation of Ampullary Adenocarcinoma and Common Bile Duct Cancer: Report of a Case and Review of Literature - Wohlauer, Max V; McManus, Martine C; Brauer, Brian; Hedges, Jeremy; Gajdos, Csaba (JOP. Journal of the Pancreas, 2012)
Context Ampullary adenocarcinomas and bile duct cancers represent a very small minority of all gastrointestinal malignancies. Synchronous presentation of both malignancies is extremely rare. Case report We report a case of a 76-year-old male who presented with painless jaundice. His work-up showed an ampullary mass and a separate common bile duct stricture. Attempted endoscopic resection established the diagnosis of ampullary adenocarcinoma. Pathologic examination of the Whipple specimen identified a separate focus of bile duct cancer. Conclusion Synchronous presentation of an ampullary mass and separate distal bile duct stricture, especially in elderly patients, should raise concern for both lesions representing malignancies. In the absence of conclusive evidence for survival advantage in resected early stage ampullary and biliary cancers, close observation should be considered a valid alternative to adjuvant chemotherapy and radiation. Image: EUS showing a hypoechoic oval mass in the ampulla.